Analysis of the Application of Criminal Law to Corporations Dumping Hazardous Waste into Environmental Media in the Supreme Court Decision (No. 1405/K/Pid.Sus./2013) - Mikael Gomgom Marisi Sihombing; Alvi Syahrin; Suhaidi Suhaidi; Mahmud Mulyadi (Inspiring Law Journal, 2025)
Environmental arrangements are regulated in Law No. 32 of 2009 concerning Protection and Management of the Environment. Corporation is a body created by law. The body that is created consists of